Potential role of 4-hydroxyisoleucine in enhancing fertility in male mice with diet-induced obesity - Nkansah, Emmanuel Osei; Lan, Yunzhu; Zhang, Hui; Xu, Binbin; Li, Qiaodan; Zafar, Mohammad Ishraq; Xu, Jian (Frontiers in Endocrinology, 2025)
BackgroundObesity is associated with hormonal imbalance, increased oxidative stress, and inflammation in the testis. These conditions adversely affect sperm quality, leading to impaired male fertility. Therefore, therapeutic interventions to counteract the adverse effects of obesity are crucial. This study explored the therapeutic effects of 4-hydroxyisoleucine (4-HIL) on fertility in male mice with diet-induced obesity.MethodsC57BL6 male mice (n=45) were randomly divided into normal diet (ND, n=15) and high-fat diet (HFD, n=30) groups for 10 weeks. The HFD group was then randomized into untreated (HFD, n=15) and 4-HIL-treated (200 mg/kg/day, intraperitoneal injection, HFD + 4-HIL group, n=15) for 6 weeks. ND and HFD controls received saline (0.3 mL/30 g body weight) throughout the intervention period. Comprehensive evaluations included (1) metabolic assessments (body weight, glucose, insulin and pyruvate tolerance tests, and blood serum lipids), (2) sperm analysis (count, concentration, and morphology), (3) fertility testing (mating trials and in vitro fertilization), (4) testicular histopathology (fat deposition and apoptosis), (5) biochemical assays (reproductive hormones, oxidative stress markers, and inflammatory cytokines), and (6) molecular analyses (mRNA sequencing and qPCR validation of differentially expressed genes).Results4-HIL treatment improved metabolic parameters, including reduced weight gain, enhanced glucose tolerance, and optimized blood serum lipids, compared to HFD controls. Treated mice exhibited superior sperm quality with increased count and concentration, reduced histomorphological abnormalities in the testis, and attenuated oxidative stress and inflammation. Furthermore, the key spermatogenic gene expressions, including spem1 and spata24, were significantly optimized in the testes of mice treated with 4-HIL compared to those of untreated mice (HFD group).ConclusionThis study demonstrates that 4-HIL therapy ameliorates obesity-induced testicular dysfunction and improves fertility markers in mice. The beneficial effects of this compound on metabolic parameters, sperm quality, and spermatogenic gene expression suggest its potential as a therapeutic agent for obesity-related male infertility. Further research is warranted to elucidate the underlying mechanisms and assess the clinical translatability of these findings.